Application of Tecnomatix Plant Simulation for modeling production and logistics processes - Siderska, Julia (Business, Management and Economics Engineering, 2016)
The main objective of the article was to present the possibilities and examples of using Tecnomatix Plant Simulation (by Siemens) to simulate the production and logistics processes. This tool allows to simulate discrete events and create digital models of logistic systems (e.g. production), optimize the operation of production plants, production lines, as well as individual logistics processes. The review of implementations of Tecnomatix Plant Simulation for modeling processes in production engineering and logistics was conducted and a few selected examples of simulations were presented. The author’s future studies are going to focus on simulation of production and logistic processes and their optimization with the use of genetic algorithms and artificial neural networks.